Phenformin-induced lactic acidosis in diabetic patients - Assan, R.; Heuclin, C.; Girard, J. R.; LeMaire, F.; Attali, J. R. (Diabetes (New York, N.Y.), 1975)
Phenformin-induced lactic acidosis in diabetic patients. R Assan , C Heuclin , J R Girard , F LeMaire and J R Attali Abstract Eighteen diabetic patients with lactic acidosis (L.A.) were analyzed for possible causal factors, metabolic changes, and efficacy of treatment. An antecedent phenformin therapy was performed in fifteen cases and was associated with renal insufficiency in ten cases and liver disease in eight cases. Tissular anoxia of primary hemodynamic or respiratory origin was absent in all cases. The severe metabolic acidosis (pH m.93 +/- 0,03; HCO3-= 6 +/- 1 MM; PaCO2 = 18 +/- 2 MM. Hg) and hyperlactatemia (14.2 +/- 0.3 mM) were associated with high lactate/pyruvate ration (70 +/- 22). High alanine levels (up to 4.6 mM) were measured in some of these patients. High beta-hydroxybutrate levels were sometimes measured (up to 7.6 mM), and substantial amounts of acetoacetate were also detected in twelve cases. Glucagon level was always increased (1,050 +/- 240 pg./ml.), and insulin/glucagon ratio was low. Cortisol (49 +/- 10 mug./100 ml.) and HGH (10.8 +/- 0.6 ng./ml.) were also elevated. Increased plasma levels of phenformin were measured in five L.A. diabetic subjects (50 +/- 5 mug./ml.) by comparison with other phenformin-treated diabetic subjects. The specificity of the assay was investigated, and phenformin metabolites were characterized by thin-layer chromatography. Por the treatment of L.A., adjunction of dialysis and furosemide improved the efficacy of early and massive sodium bicarbonate infusion. It is suggested that accumulation of phenformin via renal insufficiency plays a determinant role in causing L.A. through an impairment of lactate metabolism in the liver. An accelerated epuration of the drug may be helpful in therapy of L.A. Phenformin treatment should be avoided in case of renal and/or liver insufficiency.